Mandibular biomechanics of Crocuta crocuta, Canis lupus, and the late Miocene Dinocrocuta gigantea (Carnivora, Mammalia) - Tseng, Zhijie Jack; Binder, Wendy J. (Zoological Journal of the Linnean Society, 2009)
Tseng, Zhijie Jack, Binder, Wendy J. (2010): Mandibular biomechanics of Crocuta crocuta, Canis lupus, and the late Miocene Dinocrocuta gigantea (Carnivora, Mammalia). Zoological Journal of the Linnean Society 158 (3): 683-696, DOI:10.1111/j.1096-3642.2009.00555.x, URL: http://dx.doi.org/10.1111/j.1096-3642.2009.00555.x